Acetyl-CoA carboxylase 1 and 2 inhibition ameliorates steatosis and hepatic fibrosis in a MC4R knockout murine model of nonalcoholic steatohepatitis - Matsumoto, Mitsuharu (PLoS One, 2020)
Acetyl-CoA carboxylase (ACC) catalyzes the rate-limiting step in de novo lipogenesis, which is increased in the livers of patients with nonalcoholic steatohepatitis. GS-0976 (firsocostat), an inhibitor of isoforms ACC1 and ACC2, reduced hepatic steatosis and serum fibrosis biomarkers such as tissue inhibitor of metalloproteinase 1 in patients with nonalcoholic steatohepatitis in a randomized controlled trial, although the impact of this improvement on fibrosis has not fully been evaluated in preclinical models. Here, we used Western diet-fed melanocortin 4 receptor-deficient mice that have similar phenotypes to nonalcoholic steatohepatitis patients including progressively developed hepatic steatosis as well as fibrosis. We evaluated the effects of ACC1/2 inhibition on hepatic fibrosis. After the confirmation of significant hepatic fibrosis with a 13-week pre-feeding, GS-0976 (4 and 16 mg/kg/day) treatment for 9 weeks lowered malonyl-CoA and triglyceride content in the liver and improved steatosis, histologically. Furthermore, GS-0976 reduced the histological area of hepatic fibrosis, hydroxyproline content, mRNA expression level of type I collagen in the liver, and plasma tissue metalloproteinase inhibitor 1, suggesting an improvement of hepatic fibrosis. The treatment with GS-0976 was also accompanied by reductions of plasma ALT and AST levels. These data demonstrate that improvement of hepatic lipid metabolism by ACC1/2 inhibition could be a new option to suppress fibrosis progression as well as to improve hepatic steatosis in nonalcoholic steatohepatitis.